2002
DOI: 10.1090/conm/311/05451
|View full text |Cite
|
Sign up to set email alerts
|

On the genus of a random Riemann surface

Abstract: Brooks and Makover introduced an approach to random Riemann surfaces based on associating a dense set of them -Belyi surfaces -with random cubic graphs. In this paper, using Bollobas model for random regular graphs, we examine the topological structure of these surfaces, obtaining in particular an estimate for the expected value of their genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 0 publications
4
14
0
1
Order By: Relevance
“…cross-metric surfaces as equal if some self-homeomorphism of the surface maps one to the other. This refines the model introduced by Gamburd and Makover [24]. Here is our precise result:…”
Section: Shortest Cellular Graphs With Prescribed Combinatorial Mapssupporting
confidence: 84%
See 1 more Smart Citation
“…cross-metric surfaces as equal if some self-homeomorphism of the surface maps one to the other. This refines the model introduced by Gamburd and Makover [24]. Here is our precise result:…”
Section: Shortest Cellular Graphs With Prescribed Combinatorial Mapssupporting
confidence: 84%
“…We remark that beyond the extremal qualities that concern us, random surfaces and their geometry have been heavily studied recently [24,45] in connection to quantum gravity [49] and Belyi surfaces [3].…”
Section: Short Pants Decompositionsmentioning
confidence: 99%
“…Using this fact, one can estimate the expected value of the genus. This was done by Gamburd and Makover in [10], Brooks and Makover in [6], Pippenger and Schleich in [16] and Gamburd in [9]. We state the version of Brooks and Makover here.…”
Section: 21mentioning
confidence: 99%
“…This suggests that the injectivity radius around a typical point is growing to infinity. Gamburd and Makover [GM02] showed that as N grows the genus will converge to N/4 and using the Euler's characteristic the average degree will grow to infinity. Take a uniform measure on triangulations with N triangles conditioned on the genus to be CN for some fixed C < 1/4, then we conjecture that as N grows to infinity the random surface will locally converge in the sense of [BS01b] (see section 5 above) to a random triangulation of the hyperbolic plane with average degree 6 1−4C .…”
Section: Circle Packingmentioning
confidence: 99%